An Analysis of the Offences Committed by Youths in Selected Remand Homes in South West Nigeria, Implication for School Administrators - Adegun, O. A. (Mediterranean Journal of Social Sciences, 2013)
This study analysed the offences committed by youths who are in remand homes in the South West zone Prison arrangementin Nigeria and its implication for school administrators. The analyses are based on the type of offence, the seriousness thesociety attached to the prevalence of the offences and the causes of the offences. The South-West Prison arrangement forjuvenile offenders in Nigeria is made up of Ilorin as the headquarters and all the other remand homes in the six states of theSouth West. The prevalence of serious offences among the youths in the Nigerian society today appears to be embarrassingto parents and educators that solutions via researches are urgently needed. The sample for the study consisted of all theinmates in the remand homes in Akure (Ondo State), Abeokuta (Ogun State) and Ilorin (Kwara State). All inmates in theremand homes were selected because their number was few. The total number according to the inmates superintendent was100 and their ages spread between 10 to 18 years. The Expo-facto research design was used for the study. The researchinstrument were structured interview and a recording profoma which were applied to gather data using person to personcontact with researcher and inmate superintendent six research questions were raised for the study. Simple percentagescores, frequency counts, pictograms and charts was used to analyse the questions. The result from the descriptive analysesshowed that youths commit such offences as stealing, loitering around, burglary and violent behaviour among others. It wasdiscovered that stealing is the commonest offence committed by youths. Broken homes, poverty, peer influence and lack ofproper monitoring are the causes of these offences. It was recommended that youths should be well catered for and properlymonitored by the parents, teachers and the school. Schools should also make efforts to offer support programmes that cancater for the needs of youths in their custody. The school system should inculcate right, morals and valves in the young ones.